Erosive cola-based drinks affect the bonding to enamel surface: an in vitro study - Casas-Apayco, Leslie (2014)
Objective: This study aimed to assess the impact of in vitro erosion provoked by different cola-based drinks (Coke types), associated or not with toothbrushing, to bonding to enamel. Material and methods: Forty-six bovine enamel specimens were prepared and randomly assigned into seven groups (N=8): C- Control (neither eroded nor abraded), ERO-RC: 3x/1-minute immersion in Regular Coke (RC), ERO-LC: 3x/1-minute immersion in Light Coke (LC), ERO-ZC: 3x/1-minute immersion in Zero Coke (ZC) and three other eroded groups, subsequently abraded for 1-minute toothbrushing (EROAB-RC, EROAB-LC and EROAB-ZC, respectively). After challenges, they were stored overnight in artificial saliva for a total of 24 hours and restored with Adper Single Bond 2/Filtek Z350. Buildup coronal surfaces were cut in 1 mm2-specimens and subjected to a microtensile test. Data were statistically analyzed by two-way ANOVA/Bonferroni tests (a=0.05). Failure modes were assessed by optical microscopy (X40). The Interface of the restorations were observed using Confocal Laser Scanning Microscopy (CLSM). Results: All tested cola-based drinks significantly reduced the bond strength, which was also observed in the analyses of interfaces. Toothbrushing did not have any impact on the bond strength. CLSM showed that except for Zero Coke, all eroded specimens resulted in irregular hybrid layer formation. Conclusions: All cola-based drinks reduced the bond strength. Different patterns of hybrid layers were obtained revealing their impact, except for ZC.